Synergies and Trade-Offs of National Conservation Policy and Agro-Forestry Management Over Forest Loss in Argentina During the Last Decade - Martinez Pastur, Guillermo José; Schlichter, Tomas Miguel; Matteucci, Silvia D.; Gowda, Juan H.; Huertas Herrera, Alejandro; Toro Manríquez, Mónica D.R.; Lencinas, María Vanessa; Cellini, Juan Manuel; Peri, Pablo Luis (Springer International Publishing, 2021)
One reason for the decline of natural forest is that many ecosystem services (ESs) are usually not priced and values were only considered provisioning services. Argentina enacted the National Law 26,331/07, which regulates protection, enrichment, restoration and management of native forests and its environmental services. The objective is to determine the ecological and sociopolitical factors that influence the dynamics of forest cover loss before and after the lawimplementation and discuss the effectiveness of conservation and forest management policies. Satellite images, national ordination, forest regions maps and other variables were combined in GIS with national databases (social, agriculture, industry) to determine the evolution of potential drivers of forest changes. The main potential drivers were: (i) population growth, (ii) road density, (iii) crops area, (iv) livestock and (v) fires. Payment of incentives by government cannot fully stop the deforestation but decrease the forest loss rate. New approaches must be considered to built-in flexibility actions according to local conditions and constraints, which are influenced by social and economic contexts. Thus, it is necessary to establish new regional policies associated with the factors linked to the loss of forest cover, in the search for sustainable management alternatives that combine economic and conservation proposals.